Different investment treaties, different effects - Clint Peinhardt; Todd Allee (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
Until recently, quantitative assessments of International Investment Agreements (IIAs) have tended to treat them as interchangeable. Such assessments assume that the only measure of investor protections encoded in IIAs is whether a treaty had been signed and/or entered into force. However, the actual investment effects of investment treaties depend greatly on context.
Keywords: 330